Young British artists from the Saatchi collection. Sensation. - Adams, B. (London : Thames and Hudson, 1997)
Almond, Darren ; Billingham, Richard ; Brown, Glenn ; Callery, Simon ; Chapman, Dinos & Jake ; Chodzko, Adam ; Collishaw, Mat ; Coventry, Keith ; Davies, Peter ; Emin, Tracey ; Evans, Cerith Wyn ; Finnegan, Paul ; Francis, Mark ; Hartley, Alex ; Harvey, Marcus ; Hatoum, Mona ; Hirst, Damien ; Hume, Gary ; Landy, Michael ; Lane, Abigall ; Langlands & Bell ; Lucas, Sarah ; Maloney, Martin ; Martin, Jason ; Miller, Alain ; Mueck, Ron ; Ofili, Chris ; Parsons, Jonathan ; Patterson, Richard ; Patterson, Simon ; Pigott, Hadrian ; Quinn, Marc ; Rae, Fiona ; Rielly, James ; Saville, Jenny ; Shonibare, Yinka ; Simpson, Jane ; Taylor-Wood, Sam ; Turk, Gavin ; Wallinger, Mark ; Wearing, Gillian ; Whiteread, Rachel
boek